Aquaponics: A Sustainable Approach to Integrated Fish and Plant Farming - Kiggundu, Nicholas; Ssemuyaba, Henry Beliga; Nakavuma, Jesca; Kayendeke, Ellen; Kyazze, Florence Birungi (Discoveries in Agriculture and Food Sciences, 2025)
Achieving food and nutritional security in East Africa (EA) and the world at large is a global goal. While efforts have been made to improve traditional food production systems, hunger and nutritional insecurity still exist. Aquaponics is a novel technology that holds promising potential to provide food and improve human nutrition by producing both fish and plants. The success of aquaponics is attributed to the beneficial symbiotic relationship among fish, plants, and nitrifying bacteria. Furthermore, independent standalone recirculating aquaculture systems (RAS) and hydroponic systems still face challenges that can be overcome by integrating them into a closed single system. Additionally, alternative economical and ecologically sustainable feed sources are on the rise, with considerable attention being given to black soldier fly larvae (BSFL). For the sustainability of aquaponic systems, water quality parameters such as pH, ammonia, dissolved oxygen, and temperature are critical. This review addresses the ongoing issue of food and nutritional insecurity in East Africa and globally, despite efforts to improve traditional food systems. Moreover, it focuses on overcoming the inefficiencies of standalone RAS and hydroponic systems by integrating them into a unified aquaponics system. Thus, it mainly covers the most used aquaponics systems. Media-filled beds (MFB), deep water culture (DWC), and nutrient film technique (NFT) comprise the hydroponic component, while fish rearing tanks form the remaining part. A total of 90 academic papers were reviewed, with 60 relevant to this study cited herein. These papers provided insights into challenges and innovations in aquaponics design and management for sustainability. In conclusion, scaling up fish-plant production in aquaponic systems is inherently linked to the size of the aquaculture setup and the availability of waste nutrients.